The Use of Technology to Improve the Quality of Education by Indonesian Researchers in Scopus Database: A Bibliometric Analysis - Rahayu Nurfadilla; Zafrullah; Muhammad Al Ikhsandi Palysa Putra; Khusnul Hatimah; Izzul Kiram Suardi; Muhammad Najib (Postgraduate, University of Mataram, 2026)
This study aims to examine research trends and developments related to the use of technology for improving educational quality by Indonesian researchers through a bibliometric analysis of Scopus-indexed publications. A total of 617 documents were retrieved through a PRISMA-based screening procedure and analyzed using Biblioshiny (R) and VOSviewer. The findings indicate a substantial increase in publication output between 2019 and 2025, reaching its highest level in 2025. Padang State University recorded the highest affiliation occurrence in the dataset, while Habibi Akhmad was identified as the most productive author with the highest local h-index. The International Journal of Emerging Technologies in Learning emerged as one of the leading publication sources, recording the highest local h-index among journals in the dataset. Highly cited publications were predominantly associated with the